Challenges and Approaches in Microbiome Research: From Fundamental to Applied - Sergaki, Chrysi; Lagunas, Beatriz; Lidbury, Ian; Gifford, Miriam L.; Schäfer, Patrick (Frontiers in Plant Science, 2018)
We face major agricultural challenges that remain a threat for global food security. Soil microbes harbour enormous potentials to provide sustainable and economically favourable solutions that could introduce novel approaches to improve agricultural practices and, hence, crop productivity. In this review we give an overview regarding the current state-of-the-art of microbiome research by discussing new technologies and approaches. We also provide insights into fundamental microbiome research that aim to provide a deeper understanding of the dynamics within microbial communities, as well as their interactions with different plant hosts and the environment. We aim to connect all these approaches with potential applications and reflect how we can use microbial communities in modern agricultural systems to realise a more customised and sustainable use of valuable resources (e.g. soil).